(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
The article presents two species of the genus Amauromyza (Diptera, Agromyzidae): A. leonuri (Spencer, 1971) and A. flavifrons (Meigen, 1830), which are widespread in Artsakh Republic. Their biological, ecological and morphological features, prevalence and intensity of infestation, as well as the types of mines are described.